Shopping center e seus impactos na circulação urbana. Estudo de caso: Center Shopping em Uberlândia, MG - Andrade, Caroline Pongitori Soares de (2005)
The work, however displayed, comes to present a reflection about spaces of the city in the scope of the planning of the urban areas, specifically in the existing relation between the use of the land and the road system and of transports. The objective is to evaluate the reciprocity between these planning instances that they search to organize the city in its peculiarities, but that they must present a mutuality relation. The target of the work consists of the evaluation of an enterprise of great size, situated in the city of Uberlândia, Minas Gerais, with potential to generate interferences of great impact in its area of insertion as much in environmental terms as in the urban circulation that, in turn, also intervenes in the urban environment. It is reality of the great and medium urban centers the problems with congestion, traffic accidents, sonorous, visual and urban pollution what it generates, loses of time, energy, productivity and human resources. Of this form, great enterprises cause impacts in the transport system, in the immediate road system and in the neighborhoods it relative to its demand and, consequently, how much it offers of these infrastructures. The amplitude of the subject allows that it is opened to some questionings, being able to be explored by several meanings. Here, it will be argue, in specific, about the urban circulation and the systems of transport. One adopted methodologies proposals for Goldner, in 1994, exclusively, treating to shopping centers; of the Company of Engineering of Traffic CET, in 1983, and the National Department of Transports DENATRAN, 2001. For elaboration of the work and confirmation of the hypothesis above, it had been necessary data that characterize study area, about the city, the place of implantation of the enterprise and to the systems of transport and legislation about traffic generation and studies of impacts. It carried research in the place that allowed the characterization of the public of shopping and the attracted trips. The study of the variables that had contributed for the attraction of trips, the distribution of these displacements and the capacity of the road system, this last one, before and after implantation of shopping, they had also been analysis objects. The quantitative studies had been carried through by statistical calculation and of the software aaSidra 2.0. Of this form, one searched to contribute for the reflection about the necessity of studies of the use of the ground in the perspective of the urban circulation during the intervention in the city and the elaboration and quantification of interferences by studies of environmental and neighborhood impact.